Synthesis of Surface Oxygen-deficient BiPO4 Nanocubes with Enhanced Visible Light Induced Photocatalytic Activity - Shi,Bingtao (2017)
The visible light driven BiPO4 nanocubes with sufficient surface oxygen deficiency were fabricated by a hydrothermal process and subsequently ultrasonic assistant Fe reduction process. The products were characterized by XRD, DRS, XPS, SEM and TEM which showed that the BiPO4 had cuboid-like shape with a smooth surface and clear edges and the oxygen vacancies were succesfully introduced on the surface of the BiPO4 nanocubes. The as prepared oxygen-deficient BiPO4 nanocubes showed greatly enhanced visible light induced photocatalytic activity in degradation of Rhodamine B. The enhanced photocatalytic performance and expanded visible light response of BiPO4 may be due to the introduction of surface oxygen vacancies which can generate the oxygen vacancies mid-gap states lower to the conduction band of BiPO4.